KONTRUKSI SOSIAL MASYARAKAT TERHADAP PRAKTIK PENGOBATAN ALTERNATIF KE KIAI DI WILAYAH PEDESAAN MADURA - Salma Laili Salsabila; Eufrasia Hanindra Putri; Wadrartul Adawiah; Ahmad Ridwan; Pambudi Handoyo (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
Religious-based alternative healing remains an important part of rural community life despite the increasing accessibility of modern medical services. This study aims to understand how rural communities in Madura construct the meaning of healing through treatment practices involving the kiai as a spiritual figure. A qualitative approach was employed through in-depth interviews with informants who held diverse perspectives regarding such healing practices. The findings indicate that healing is not understood solely as physical recovery, but also as the attainment of inner peace, a sense of security, and a strengthened spiritual connection through prayer and the blessings of the kiai. This practice also contributes to the preservation of tradition and the reinforcement of collectively inherited socio-cultural identity. Using the perspective of social construction, the analysis demonstrates that trust in the kiai is shaped through ongoing social processes, positioning kiai-based healing as a social reality that influences how people interpret health and life. The findings further reveal that seeking healing from the kiai functions not only as a curative effort but also as a space for negotiating religious values, local traditions, and social experiences within rural Madurese society.